Benefits of Green Tea Polyphenols for Kidney Health: A Literature Review - Nadia Warda Sekar Sari; Trina Ekawati Tallei; Beivy Jonathan Kolondam (Grimsa Journal of Science Engineering and Technology, 2023)
The issue of kidney health has emerged as a global public health concern. Kidneys play a vital role in eliminating toxic substances and maintaining fluid and chemical balance in the body. Preserving kidney health is tantamount to safeguarding overall bodily health, as kidney damage can adversely affect other organs and organ systems. This can give rise to various ailments and compromise one’s physical condition. Throughout ancient history, plants have been employed for medicinal purposes in treating a wide array of ailments with one such plant being tea (Camellia sinensis L). Tea is renowned for its antioxidant and anti-inflammatory properties. It contains bioactive compounds, notably polyphenols, which contribute to enhancing health. Polyphenols serve as therapeutic agents for the kidneys and can prevent the onset of other degenerative disease. Prior research has demonstrated that EGCG, a derivative of polyphenols, can safeguard the kidneys against ischemia-reperfusion injury, kidney fibrosis, and inflammation. Catechins, a subcategory of polyphenols, act as antioxidants, anti-inflammatories, and anti-apoptotic agents, thereby shielding kidney cells.